Knowledge of nursing professionals concerning pressure ulcers - Débora de Sousa Lemos; Nathalia Ingrid Crosewski; Aline Batista Maurício; Hellen Roehrs (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769211707 Objective: to identify the knowledge of nursing professionals on pressure ulcers in the Centre of Semi-intensive Therapy of a university hospital. Method: quantitative study. The data collection  occurred in December 2012 and used a questionnaire translated and validated to the Brazilian reality, with items of true or false, and satisfactory performance of 37 items (90%). Results: nursing assistants scored 30.9 (75.33%), technicians 28 (68.29%) and nurses 33.6 (81.95%). The items with fewer scores related to contraindicated nursing care: massage in areas of hyperemia, use of water gloves, inadequate repositioning of bedridden patients and wheelchair users, and elevation angle of the headboard. Conclusion: the professionals presented unsatisfactory knowledge, demonstrating the importance of updating and training professionals in service.